THE RESPONSE OF NEGATIVE STIGMA AND MOTIVATION TO RECOVER TO THE LEVEL OF ADHERENCE TO TAKING MEDICATION IN PULMONARY TUBERCULOSIS PATIENTS IN THE ANGGUR ROOM OF RSUD DR ADJIDARMO LEBAK IN 2023 - Suara, Mahyar; Azizah, Siti (HEARTY, 2025)
Background: Tuberculosis (TB) is still the leading cause of death from infectious pathogens worldwide. Some of the factors that influence this are the negative stigma against the disease, at RSUD Dr. Adjidarmo Lebak, precisely in the Anggur room in 2022, there were 466 cases of Pulmonary Tuberculosis patients. Until now there is still a growing assumption in the community that TB is a hereditary disease that is difficult to overcome. This assumption makes many TB patients do not want to seek treatment because of shame and plus the family also tends to cover up the condition of the disease, Motivation has an influence on the success of treatment, especially pulmonary TB patients so that their desire and willingness to be able to behave obediently in treatment, a person's motivation to recover can affect adherence to taking medication in tuberculosis patients. Research Objectives: Knowing the response of negative stigma and motivation to recover to the level of adherence to taking anti TB drugs in pulmonary tuberculosis patients in the anggur room of Rsud Dr. Adjidarmo Lebak in 2023. Research methods: The research method used was descriptive correlational and cross sectional method with chi square test. The sample in this study was 33 tuberculosis sufferers undergoing anti-TB drug treatment who were treated in the anggur Room in November - December. The technique used in this research is sequential sampling, and data collection using a questionnaire. Research result: The results of data processing on respondents who have a high negative stigma as much as 97%, high recovery motivation as much as 100% and a high level of compliance as much as 42%, the results of the Chi Square test Negative stigma response to the level of adherence to taking anti TB drugs obtained p value = 0.024 means p < α (0.05). So it can be concluded that Ho is rejected, and the Cure Motivation Response to the level of adherence to taking anti TB drugs obtained p value = 0.010 means p < α (0.05). So it can be concluded that Ho is rejected. Conclusions and suggestions: Statistically there is a relationship between negative stigma response and motivation to recover on the level of adherence to taking anti-tuberculosis drugs in pulmonary tuberculosis patients in the Anggur room of RSUD Dr. Adjidarmo Lebak. It is expected that the results of this study can be used as input in carrying out nursing care in order to improve the quality of nursing services in the form of providing or conducting health education, especially the importance of adherence to taking OAT in tuberculosis patients in the Anggur room of RSUD Dr. Adjidarmo Lebak, in an effort to prevent drug resistance.